Open minimally invasive versus video‐assisted minimally invasive parathyroidectomy for primary hyperparathyroidism - Smith, Matthew E (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of open minimally invasive versus video‐assisted minimally invasive parathyroidectomy for primary hyperparathyroidism.